2009
DOI: 10.2353/ajpath.2009.080503
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Depolymerization Suppresses α-Synuclein Accumulation in a Mouse Model of Multiple System Atrophy

Abstract: Multiple system atrophy (MSA) is a neurodegenerative disease caused by an accumulation of ␣-synuclein (␣-syn) in oligodendrocytes. Little is known about the cellular mechanisms by which ␣-syn accumulation causes neuronal degeneration in MSA. Our previous research, however, revealed that in a mouse model of MSA, oligodendrocytic inclusions of ␣-syn induced neuronal accumulation of ␣-syn, as well as progressive neuronal degeneration. Here we identify the mechanisms that underlie neuronal accumulation of ␣-syn in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 35 publications
(35 reference statements)
3
42
0
Order By: Relevance
“…The exogenous ␣-syn in oligodendrocytes was of human origin, and the endogenous ␣-syn in neurons was of mouse origin in the mouse CNS. These Tg mice not only recapitulated many features of MSA neuropathology but also provided evidence that formation of GCIs triggers neuronal accumulation of insoluble ␣-syn, leading to neuronal dysfunction and degeneration in the mouse CNS (10,12,13). This is consistent with the neuronal pathology in the human pathology of MSA (14).…”
Section: Multiple System Atrophy (Msa)supporting
confidence: 68%
See 4 more Smart Citations
“…The exogenous ␣-syn in oligodendrocytes was of human origin, and the endogenous ␣-syn in neurons was of mouse origin in the mouse CNS. These Tg mice not only recapitulated many features of MSA neuropathology but also provided evidence that formation of GCIs triggers neuronal accumulation of insoluble ␣-syn, leading to neuronal dysfunction and degeneration in the mouse CNS (10,12,13). This is consistent with the neuronal pathology in the human pathology of MSA (14).…”
Section: Multiple System Atrophy (Msa)supporting
confidence: 68%
“…resulted in the formation of an insoluble protein complex that progressively accumulated in the neurites of Tg neurons, leading to neuronal dysfunction (12). Furthermore, we demonstrated that accumulation of insoluble ␣-syn was suppressed by a microtubule-depolymerizing agent, indicating that free ␤-III tubulin-␣-syn molecules are less prone to inclusion formation (12,16).…”
Section: Multiple System Atrophy (Msa)mentioning
confidence: 87%
See 3 more Smart Citations